Fouling deposits in food industries: The challenges in pursuing the GBI-IEB - Norashikin, Ab. Aziz, Engr. Dr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org.my/